Potential product and economic cycles in Mexico, 1980.1-2006.4 - Loría, Eduardo; Ramos, Manuel G.; De Jesús, Leobardo (Estudios Económicos de El Colegio de México, 2008)
Through the use of Structural Times Series Models we estimated: potential output, the output gap and the business cycles for the Mexican GDP (1980.1-2006.4). We found that: a) the potential output has varied sharply for two different time periods: 2.1% (1980.4-1994.4) and 3.7% (1995.4-2006.4); b) great component of seasonality: Q1 and Q3 are of slow growth (below average) and Q2 Q4 above average; c) we detected that the peaks and troughs have been progressively less pronounced since the year 2000.